If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2z + -1) + -5(z + 6) = 2(z + 1) Reorder the terms: 5(-1 + 2z) + -5(z + 6) = 2(z + 1) (-1 * 5 + 2z * 5) + -5(z + 6) = 2(z + 1) (-5 + 10z) + -5(z + 6) = 2(z + 1) Reorder the terms: -5 + 10z + -5(6 + z) = 2(z + 1) -5 + 10z + (6 * -5 + z * -5) = 2(z + 1) -5 + 10z + (-30 + -5z) = 2(z + 1) Reorder the terms: -5 + -30 + 10z + -5z = 2(z + 1) Combine like terms: -5 + -30 = -35 -35 + 10z + -5z = 2(z + 1) Combine like terms: 10z + -5z = 5z -35 + 5z = 2(z + 1) Reorder the terms: -35 + 5z = 2(1 + z) -35 + 5z = (1 * 2 + z * 2) -35 + 5z = (2 + 2z) Solving -35 + 5z = 2 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. -35 + 5z + -2z = 2 + 2z + -2z Combine like terms: 5z + -2z = 3z -35 + 3z = 2 + 2z + -2z Combine like terms: 2z + -2z = 0 -35 + 3z = 2 + 0 -35 + 3z = 2 Add '35' to each side of the equation. -35 + 35 + 3z = 2 + 35 Combine like terms: -35 + 35 = 0 0 + 3z = 2 + 35 3z = 2 + 35 Combine like terms: 2 + 35 = 37 3z = 37 Divide each side by '3'. z = 12.33333333 Simplifying z = 12.33333333
| -6=-4n+3m | | 3(x-5)=4(x-9) | | 7x-3y+6a= | | 2x-9y+8z-39= | | 180=90+x+2x | | 0.08+0.09(x+2000)=690 | | 4r=7-2 | | -x+-1=x+-21 | | 36x+28-19=19x+11+17x-2 | | 2(2g-5)=4-(4g) | | (3x-1)+(2x-5)= | | 38.2*j=0.573 | | lnx=0.41 | | 9x+7=13x-1 | | 45=10-7a | | 81=11x+4 | | 6a-8-9a-5= | | -2(x-2)=8-3-x | | 9y=22 | | f=(f+12)+(f+60) | | 2x^2-500x=40000 | | 64a=9*320 | | 110=39.02+.25x | | 64*3=a*320 | | 10y+6=6+10y | | -3x-7=25 | | .03(x)+.09(y)-750=14000 | | 64*a=3*320 | | x^2-80x+400=0 | | 63+-x=2x+3 | | JOSE+JOSE= | | 7y+7=7y+8 |